Peningkatan Kualitas Sensori Sari Buah Pala melalui Penambahan Kapur, Kitosan, dan Gula - Breemer, Rachel (Universitas Pattimura, 2025)
This study aimed to investigate the effect of the interaction among lime (calcium hydroxide), chitosan, and sugar on the sensory quality of nutmeg juice, and to determine the optimal formulation for quality enhancement. Nutmeg fruit pulp, which is largely underutilized and exhibits sensory limitations such as astringency, readily degradable volatile aroma, and poor color clarity, was processed into juice. The research employed a Completely Randomized Design (CRD) with a 3 × 3 × 3 factorial pattern, utilizing three concentration levels for lime (1%, 2%, 3%), chitosan (0.1%, 0.15%, 0.2%), and sugar (15%, 20%, 25%). Results of the hedonic sensory evaluation indicated that the interaction of the three additives exerted a significant effect on astringency, color (turbidity), aroma, and overall acceptability. The A2B3C3 formulation (2% Lime, 0.2% Chitosan, 25% Sugar) yielded the highest scores for a very non-astringent taste (3.94) and low turbidity (3.47). Nevertheless, the best formulation preferred by panelists for overall acceptability was A2B2C3 (2% Lime, 0.15% Chitosan, 25% Sugar) with a mean score of 3.43 (liked). This confirms that an optimal combination of these food additives can establish a superior sensory balance, positioning nutmeg juice as a product with high potential for commercial development.